Holocene reef accretion on the Rodrigues carbonate platform: An alternative to the classic “bucket-fill” model - O'Leary, Mick; Perry, C. (Geological Society of America, 2010)
Carbonate platform evolution around the island of Rodrigues, southwestern Indian Ocean, is reconstructed from cores recovered across the platform's windward margin. In contrast to the classic "bucket-fill"model of carbonate platform evolution, whereby platform filling occurs predominantly as a function of the lagoonward transport of sediment from the reef rim, data from Rodrigues demonstrate that the primary mode of platform filling was through reef progradation from the platform interior seaward. Indeed, radiocarbon dates indicate that much of the platform interior had filled by ~2000 cal. (calibrated) yr B.P. Data also indicate that the reef rim probably caught up with sea level only in the past ~1000 yr, and subsequent export of sediment from those areas into the lagoon has probably only become important during the final stages of the platform's evolution. We interpret this as a function of the platform margin reef's catch-up growth mode. This would have allowed significant marine circulation within the platform interior, thus promoting active reef growth prior to sea level being attained. Given that such catch-up growth modes are widely recognized on many reef/platform margins, we suggest that this novel platform evolutionary model may have widespread applicability